Ideologi dan Hegemoni dalam Shalawatan (Study ff The Ideology of Althusser and Gramsci's Hegemony) - M. Ahsana Ghazalba (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
This study aims to describe the ideological meaning and the form of hegemonicism in the prayers of the popular Javanese people of their time. Analytical choice The ideological state apparatus initiated by Althusser is used to uncover the play of ideological meaning in prayer. While discussing the Gramsci hegemony, it is used to discuss the domination of the ideological state apparatus. This research method is descriptive qualitative. The object that is read is the meaning of persuasion, identity, appreciation, and punishment in prayer through the study of the state apparatus and hegemony. The result of this research are offer processes containing idealist that have the ability, identification, appreciation and punishment in shalling moral, ethical, and religious people.Keywords: Ideology; hegemony; shalawatan; meaning; identity. IntisariPenelitian ini bertujuan untuk mendeskripsikan makna ideologis dan bentuk penghegemonian dalam shalawatan masyarakat Jawa yang populer di zamannya. Pendekatan analitis Ideological state aparatus yang digagas oleh Althusser digunakan untuk mengungkap permainan makna ideologis dalam shalawatan. Sedangkan pendekatan hegemoni Gramsci digunakan untuk menyoroti pendominasian dari berjalannya Ideological state aparatus. Metode penelitian ini adalah deskriptif kualitatif. Objek yang diteliti adalah makna persuasif, identity, reward, dan punishment dalam shalawatan melalui kajian Ideological state apparatus dan hegemoni. Hasil dari penelitian ini adalah bahwa shalawatan merupakan gagasan ideologis yang memiliki sifat persuasif, identity, reward, dan punishment dalam membentuk masyarakat Jawa yang bermoral, beretika, dan religius.Kata kunci: Ideologi; hegemoni; shalawatan; makna; identitas.